The Voice of the Germans in the International Writers’ Congress for the Defence of Culture (1935 and 1937) - Cañadas García, Teresa (Revista de Filología Alemana, 2011)
Many of the German artists who were forced into exile by the Nazi rise to power did not hesitate to bring all their artistic skills into play to fight Fascism. They were joined by artists from many other countries. The 1st and 2nd International Writers’ Congress for the Defence of Culture, held on 1935 and 1937 respectively, were proof of the desire for unity between writers of different nationalities in the fight against Fascism. This article analyses German thinking seen through the contributions of writers in both congresses.
Keywords: International Writers’ Congress for the Defence of Culture; German antifascist exile; Spanish Civil War.